A multi-node adaptive load balancing approach for availability in cloud computing - Kamal idrissi, Hamza; Kartit, Ali (International Journal of Engineering and Technology, 2018)
Cloud computing has become one of the most important fields in the IT technology domain. Its main objectives are to deliver different services for users, such as infrastructure, platform or software with a reasonable and more and more decreasing cost for the clients. In order to meet those objectives many aspects are studied and are subject to research, the availability is certainly one of the key sides of the Cloud Computing. Load balancing techniques deal with many aspects of the cloud such as performance, response time, … For the big distributed cloud systems that deal with many clients and big amounts of data and requests, load balancing is essential in order to properly satisfy all the demands. In this paper, we address the subject of availability with an adaptive load balancing approach in cloud computing. This proposed approach ensures load balancing as well as the availability of the system while avoiding points of failure.
Keywords: Adaptive Load Balancing; Availability; Cloud Computing; Multiple Nodes.